Development of Augmented Reality Learning Media Based on Spatial Thinking Skills - Mei Vita Romadhon Ningrum; Ummi Saadah Ardianna (TEPIAN, 2025)
Fire is one of the most common disasters, and the denser the population, the higher the risk of fire. One area that has a high fire potential is the densely populated city of Samarinda. One way to mitigate or prevent fire hazards is by utilizing the learning process at school, especially in geography subjects. The purpose of this research is to produce augmented reality media design based on spatial thinking skills on fire disaster mitigation material and to determine the feasibility of using augmented reality learning media based on spatial thinking skills in geography subjects. This research is development research, where the developed media is tested to material experts and media experts before being tested on students. Data analysis used qualitative and quantitative methods, with quota sampling techniques. The results showed that the product in the form of 3D Augmented Reality (AR) learning media application named ‘AR Fire Mitigation’ can be used on smartphones. This application is offline and does not require internet access. This product is also equipped with a supporting book that contains 2D and 3D images with explanations for each material. The supporting book discusses fire disaster mitigation materials, including the characteristics of fire-prone and non-fire-prone areas, the impact of fires, types of fires, classification of fires, mitigation during a fire, causes of fires, fire disaster mitigation scenarios, and conditions of residential and land fires. The learning media developed is considered feasible based on the average results of user trials of 88.92%, so that the learning media products and supporting books produced are categorized as feasible.